TRADITIONAL VALUES AS A NATIONAL SECURITY FACTOR IN THE AGE OF GLOBALIZATION - KOTLYAROVA, Victoria; RUDENKO, Andrei; PONOMAREV, Petr (CENTRAL ASIA AND THE CAUCASUS, 2017)
The authors have undertaken an in-depth investigation of traditional values as factors of national security of states in the age of globalization and the changes in the axiological system of society and value orientations of its members, caused by globalization. The authors relied on a wide spectrum of methodological and theoretical approaches, used in philosophy, political science, sociology, and globalistics. In the context of the unfolding civilizational evolution, globalization can be described as a relatively recent and, at the same time, highest development stage of the familiar process of internationalization (transnationalization) of many aspects of social life. In the last thirty-odd years, globalization has been unfolding as cultural and axiological impacts of Westernization and expansion of Western values to non-Western countries. In many cases, the destroyed traditional values and traditional foundations of life activities are not replaced with adequate axiological principles of development and modernization. The branching off of contemporary culture into two directions (globalization and regionalization) can be felt at all levels and, according to the present authors, have already created two paradoxes—preservation of the cultural heritage and coexistence of cultures. In Russia, globalization is spreading the easiest in the sphere, affected by the motives and symbols of material consumption. The multiplying signs of inefficiency of state regulation in market economy and the widening gap between the rich and poor can be considered as another powerful impetus for the spread of globalization. On the other hand, the fact that the traditional values are gaining popularity is the most important evidence that in Russia globalization is negatively assessed. In the epoch of globalization, traditional values keep the flood of unification and homogenization within certain limits.